Peut-On Se Passer Du Concept D’ecosysteme ? Partie I : Questions Epistemologiques Et Methodologiques - Thierry Rolland (European Scientific Journal, ESJ, 2018)
The concept of ecosystem played a central role in the structuring of ecology as a full-fledged scientific discipline during the twentieth century. However, certain theoretical and practical issues related to the notions of homogeneity and stability on one side and dynamic equilibrium on the other led, from an artefactual a priori, to exclude relevant phenomena from the field of analysis, such as maintaining ecosystems subject to conditions of permanent change. In this first article, after a historical and epistemological analysis of the heuristic value and the limits of the concept of ecosystem, some tracks are proposed in the direction of its maintenance by removing the ambiguities that accompany it since its origins.